2005
DOI: 10.1007/s11012-005-5875-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Rocking Behavior of Rigid Objects

Abstract: Abstract.A novel formulation for the rocking motion of a rigid block on a rigid foundation is presented in this work. The traditional piecewise equations are replaced by a single ordinary differential equation. In addition, damping effects are no longer introduced by means of a coefficient of restitution but understood as the presence of impulsive forces. The agreement with the classical formalism is very good for both free rocking regime and harmonic forcing excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…1 46,53,54,59,60] to cite a few. In parallel, the field of impact dynamics has witnessed an intense activity in the past 25 years; see, e.g., [8-10, 15, 18-20, 29, 31, 38, 48, 52, 66] and references therein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 46,53,54,59,60] to cite a few. In parallel, the field of impact dynamics has witnessed an intense activity in the past 25 years; see, e.g., [8-10, 15, 18-20, 29, 31, 38, 48, 52, 66] and references therein.…”
mentioning
confidence: 99%
“…They found good agreements between their simulations and their experiments. Pena and Prieto et al [42,43,46] performed many experiments and also proposed a new model for rocking. It is noteworthy that in their experiments that Pena et al [42] found better matching between the above value of r and the experimental values, which differ by much smaller percentage than in [7,45].…”
mentioning
confidence: 99%
“…Several approaches for the design of a rocking structure have also been proposed [18,19]. Prieto and Lourenço [20] described the impact effect of a rocking rigid block on a rigid base using the D'Alembert principle. Attention was seldom paid to the footing response, especially the contact force at the interface between the footing and the underlying soil.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of analytical studies on the impact mechanism due to uplift have been conducted. Prieto and Lourenço [20] described the impact effect of a rocking rigid block on a rigid base using the D'Alembert principle. They pointed out that the impacts make the total energy of a rocking block no longer equal to the sum of kinetic and potential energy.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have used the simple model of Housner to investigate analytically and numerically the rocking response of rigid blocks subjected to a seismic action as well as their stability [2,3,4,5], while others have defined a new formulation to unify the piecewise equation describing the rocking motion [6] or developed numerical tools based on the Discrete Element Method (DEM) to model the rigid block [7].…”
Section: Introductionmentioning
confidence: 99%